2022
DOI: 10.1002/ppp3.10251
|View full text |Cite
|
Sign up to set email alerts
|

Assessing extinction risk across the geographic ranges of plant species in Europe

Abstract: Societal Impact Statement Plants play fundamental roles in ecosystems, yet merely 10% of species have an assessment of their global extinction risk. Through the integration of national Red Lists and comprehensive global plant distribution data, we identify previously unassessed plant species in Europe that are threatened throughout their geographic range and thus at risk of global extinction. Our workflow can be replicated to facilitate the integration of disparate national monitoring efforts around the world … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…While the importance of jurisdictional responsibility, endemic species, and species irreplaceability has been identified as priorities for conservation for over two decades (Gauthier et al, 2010; Margules & Pressey, 2000; Myers et al, 2000; Schmeller et al, 2008), they are not yet clearly reflected in national prioritization exercises and conservation actions. The majority of threatened vascular plants in Europe are single‐country endemics, but only 16% have Red List assessments (Holz et al, 2022). An Australian study found that only 6.8% of endemic plants, 9.4% of endemic birds, and 28.9% of endemic mammals have been assessed under the Environment Protection and Biodiversity Conservation Act 1999 (Alfonzetti et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While the importance of jurisdictional responsibility, endemic species, and species irreplaceability has been identified as priorities for conservation for over two decades (Gauthier et al, 2010; Margules & Pressey, 2000; Myers et al, 2000; Schmeller et al, 2008), they are not yet clearly reflected in national prioritization exercises and conservation actions. The majority of threatened vascular plants in Europe are single‐country endemics, but only 16% have Red List assessments (Holz et al, 2022). An Australian study found that only 6.8% of endemic plants, 9.4% of endemic birds, and 28.9% of endemic mammals have been assessed under the Environment Protection and Biodiversity Conservation Act 1999 (Alfonzetti et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Species of conservation concern. We identified species of conservation concern using two criteria: (1) Species listed as threatened in national Red Lists based on a recent database synthesizing national Red Lists across Europe 92 . That is, we determined the threat status of each species at a given site based on the respective national Red List of the country in which that site was located (based on IUCN threat classifications, see ref.…”
Section: Response Variablesmentioning
confidence: 99%
“…We identified species of conservation value using two criteria: (1) Species listed as threatened in national Red Lists based on a recent database synthesizing national Red Lists across Europe 85 . That is, we determined the threat status of each species at a given site based on the respective national Red List of the country in which that site was located (based on IUCN threat classifications, see ref.…”
Section: Species Of Conservation Valuementioning
confidence: 99%